2010
DOI: 10.1007/s12602-010-9041-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of GP21 and GP12: Two Potential Probiotic Bacteria Isolated from the Gastrointestinal Tract of Atlantic Cod

Abstract: This study evaluated the probiotic potential of GP21 (Pseudomonas sp.) and GP12 (Psychrobacter sp.), two bacteria isolated from the intestinal tract of a cold-water fish, Atlantic cod. The antagonistic activity of the two intestinal bacteria against two fish pathogens (Vibrio anguillarum and Aeromonas salmonicida subsp. salmonicida) was studied under different physical conditions. Further, their resistance to physiological barriers and their ability to form biofilms were examined. In addition, a test was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 33 publications
3
36
0
1
Order By: Relevance
“…Despite this down-regulation of cytokine expression increased survival, increased weight gain, decreased cortisol levels and improved stress responses were monitored [192]. In Atlantic cod autochthonous intestinal bacteria also appeared to be potential probionts [193] and proteomic analysis of probiotic stimulated cod indicated a lower level of immune stimulation but an up-regulation of proteins involved in growth and development [194]. It will be clear that the data given on probiotic stimulation are fragmentary and probably bacterial strain or fish species dependent and hence much more research is necessary to explain the protection reported after feeding probiotics.…”
Section: Gut Microbiota and Probiotic Immune-stimulationmentioning
confidence: 99%
“…Despite this down-regulation of cytokine expression increased survival, increased weight gain, decreased cortisol levels and improved stress responses were monitored [192]. In Atlantic cod autochthonous intestinal bacteria also appeared to be potential probionts [193] and proteomic analysis of probiotic stimulated cod indicated a lower level of immune stimulation but an up-regulation of proteins involved in growth and development [194]. It will be clear that the data given on probiotic stimulation are fragmentary and probably bacterial strain or fish species dependent and hence much more research is necessary to explain the protection reported after feeding probiotics.…”
Section: Gut Microbiota and Probiotic Immune-stimulationmentioning
confidence: 99%
“…Several host-derived candidate probiotics have been characterized both from coldwater (Lazado et al, 2010c;Brunt et al, 2007;Spanggaard et al, 2001;Robertson et al, 2000;Gildberg and Mikkelsen, 1998;Jöborn et al, 1997) and warm-water fish species (Lara-Flores and Olvera-Novoa, 2013; Chantharasophon et al, 2011;Ghosh et al, 2007;Kumar et al, 2006). On the course of exploring new probiotic microorganisms, the attention was directed to the commensal microorganisms of the host.…”
Section: Host-derived Probioticsmentioning
confidence: 99%
“…LAB isolates from the gut of tilapia had higher antagonistic activity from extra cellular protein (ECP), putatively bacteriocin compared to the intracellular protein (ICP) against A. hydrophila (Vijayabaskar and Somasundaram, 2008). ), candidate probiotics from the intestinal microbiota of Atlantic cod (Lazado et al, 2010c). Inhibitory activity of the extracellular supernatant was also identified in GP21 (Pseudomonas sp.)…”
Section: Production Of Inhibitory Compoundsmentioning
confidence: 99%
See 2 more Smart Citations